Reorientasi Pembinaan KUD - Sunartiningsih, Agnes (Jurnal Ilmu Sosial dan Ilmu Politik, 1998)
The existence of cooperative in Indonesia, especially in rural area, has been known in long period. At the beginning of the New Order period, rural community had been introduced to the government cooperative, the Village Unit Cooperation (KUD), From the time that, the existence of KUD that was not based on the initiative of local community, has been in crisis when its performance has not been reflected its mission as the central pillar (soko guru) of rural economy activities. Therefore, it need re-orientation of KUD in order to vitalize the existence of cooperative.